KEBAHAGIAAN PASIEN RUMAH SINGGAH GAJAH MADA DINAS SOSIAL SURAKARTA (Lembaga Pengembangan Kinerja Dosen, 2023)
Happiness is an important psychological aspect in the recovery and well-being of the patient. A positive emotional state, a feeling of satisfaction, and a good quality of life greatly contribute to the successful treatment and recovery of the patient,.It is therefore important to understand the factors that influence the happiness of patients in Surakarta social service halfway housesThis study aims to explore and analyze the fulfillment of patient happiness in social service halfway house Surakarta. the research method in this writing is qualitative with interview / interview, and observation. On the happiness of patients Gajah Mada halfway house surakarta social services. The results of the study patient happiness halfway house gajah Mada social service Surakarta feel quite good happiness while living while in a halfway house due to the fulfillment of the needs of food ,drink and clothing that much.patients feel comfortable during worship.